Analisis Risiko Asupan Makronutrien Terhadap Kejadian Stunting Pada Bayi Usia 7–12 Bulan Di Puskesmas Barabaraya Makassar - Nur Ulmy Mahmud; Suchi Avnalurini Shariff (Window of Public Health Journal, 2023)
Weight gain is an important indicator of infant growth and health, influenced by adequate nutrition and parenting practices. This study aimed to analyze the risk factors for growth disorders among infants aged 7–12 months in the working area of Barabaraya Community Health Center. This analytical observational study used a case-control design. The sample consisted of 30 cases and 30 controls selected through purposive sampling with matching based on infant gender. Data were collected through interviews using questionnaires on maternal characteristics, breastfeeding patterns, parenting styles (PSDQ), and 1x24-hour food recall to assess dietary intake. The study was conducted from August to September 2023. The results showed that antenatal care (ANC) (OR=12.429; 95% CI=1.461–105.737), permissive parenting style (OR=1.313; 95% CI=0.472–3.653), protein intake (OR=1.306), and carbohydrate intake (OR=1.529; 95% CI=0.536–4.361) increased the risk of infant growth disorders, although the associations were not statistically significant. Meanwhile, parity (OR=0.868; 95% CI=0.306–2.461), democratic parenting style (OR=0.571; 95% CI=0.201–1.624), authoritarian parenting style (OR=0.550; 95% CI=0.157–1.931), breastfeeding patterns (OR=0.669; 95% CI=0.242–1.852), energy intake (OR=0.048; 95% CI=0.010–0.238), and fat intake (OR=0.400; 95% CI=0.118–1.360) acted as protective factors, although no significant relationships were found. This study concludes that ANC, permissive parenting style, and protein and carbohydrate intake are risk factors for infant growth disorders.